A day of history and hope: A critical discourse analysis of Joe Biden’s Inauguration speech - Pramadya, Teguh Puja; Rahmanhadi, Anna Desiyanti (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2021)
This article explores how President-elect Joe Biden used the rhetoric of political language in his inauguration speech as an attempt to showcase his policy plans as well as his political views on the American political scene. This article also looks at how each of the political messages in his inauguration speech shows the ideology and power that Joe Biden believes in. To provide comprehensive details about the elements of Joe Biden’s inauguration speech, the researchers use Norman Fairclough’s idea to view continuing social practice via the prisms of text, discourse practice, and the sociocultural practice that underpins the text, or to view the underlying reality that gave rise to the discourse